Distribution of Glycerol Dialkyl Glycerol Tetraethers (GDGTs) in Microbial Mats From Holocene and Miocene Sabkha Sediments - Petrick, Benjamin; Reuning, Lars; Martínez-García, Alfredo (Frontiers in Earth Science, 2019)
Sabkhas are important settings for understanding early earth biological environments, and the algal mats associated with them are thought to be potential source rocks for hydrocarbon production. In this study we compare the sedimentological facies and distribution of branched, and isoprenoid glycerol dialkyl glycerol tetraethers (GDGTs) in modern and mid-Holocene sabkha sediments from Abu Dhabi with well-preserved Miocene (12–13 Ma) sabkha sediments recently recovered at IODP site U1464 off the north coast of Australia. We show that the facies of the Miocene sediments is very similar to Holocene and modern sabkhas. Furthermore, we show that there are distinct patterns of isoprenoid GDGT distributions in the modern sabkha and that these patterns are well preserved in both the buried Holocene and the Miocene algal mats. The sabkha sediments analyzed are characterized by high %GDGT-0 and methane index, dominance of branched GDGTs over crenarchaeol (high BIT index), an unusual distribution of isoprenoid GDGTs 1–3, and also low abundance of archeol. The distribution of branched GDGT differs between modern and Miocene sabkhas and is similar in Miocene sabkha and non-sabkha sediments suggesting that they may be of limited use to distinguish paleo-sabkha sediments. Overall, isoprenoid GDGT distributions appear to be different from those found in modern soils, lakes and marine sediments, as well as from those found in Miocene shallow water sediments right below the sabkha, therefore they could be used in combination with facies analysis to identify paleo-sabkha environments in sedimentary sequences.